Analyzing the epidemiological outbreak of COVID‐19: A visual exploratory data analysis approach - Dey, Samrat K.; Rahman, Md. Mahbubur; Siddiqi, Umme R.; Howlader, Arpita (Journal of medical virology, 2020)
There is an obvious concern globally regarding the fact about the emerging coronavirus 2019 novel coronavirus (2019‐nCoV) as a worldwide public health threat. As the outbreak of COVID‐19 causes by the severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2) progresses within China and beyond, rapidly available epidemiological data are needed to guide strategies for situational awareness and intervention. The recent outbreak of pneumonia in Wuhan, China, caused by the SARS‐CoV‐2 emphasizes the importance of analyzing the epidemiological data of this novel virus and predicting their risks of infecting people all around the globe. In this study, we present an effort to compile and analyze epidemiological outbreak information on COVID‐19 based on the several open datasets on 2019‐nCoV provided by the Johns Hopkins University, World Health Organization, Chinese Center for Disease Control and Prevention, National Health Commission, and DXY. An exploratory data analysis with visualizations has been made to understand the number of different cases reported (confirmed, death, and recovered) in different provinces of China and outside of China. Overall, at the outset of an outbreak like this, it is highly important to readily provide information to begin the evaluation necessary to understand the risks and begin containment activities. Highlights The outbreak of COVID‐19 has become a clinical threat worldwide. Knowledge about SARS‐CoV‐2 virus remains limited. Epidemiological data needs to be analyzed. A Visual Exploratory Data Analysis (V‐EDA) model helps to understand the consequences of the COVID‐19 outbreak.